2017
DOI: 10.3390/cancers9030021
|View full text |Cite
|
Sign up to set email alerts
|

AR Signaling in Breast Cancer

Abstract: Androgen receptor (AR, a member of the steroid hormone receptor family) status has become increasingly important as both a prognostic marker and potential therapeutic target in breast cancer. AR is expressed in up to 90% of estrogen receptor (ER) positive breast cancer, and to a lesser degree, human epidermal growth factor 2 (HER2) amplified tumors. In the former, AR signaling has been correlated with a better prognosis given its inhibitory activity in estrogen dependent disease, though conversely has also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 172 publications
(239 reference statements)
2
57
0
Order By: Relevance
“…About 50%-80% of invasive breast cancers (regardless of ER status) express AR and recent studies indicate AR expression is positively associated with a good prognosis. In addition, recent studies showed that AR-expressing triple-negative breast cancer (TNBC) is dependent on AR signaling; thus, targeting AR seems to improve outcomes in TNBC (1)(2)(3)(4)(5)(6)(7). Despite the prevalence and clinical significance of AR expression in breast cancer, preclinical evidence supporting the use of ARtargeting agents and potential biomarkers of response to AR inhibitors in breast cancer are lacking (4).…”
Section: Introductionmentioning
confidence: 99%
“…About 50%-80% of invasive breast cancers (regardless of ER status) express AR and recent studies indicate AR expression is positively associated with a good prognosis. In addition, recent studies showed that AR-expressing triple-negative breast cancer (TNBC) is dependent on AR signaling; thus, targeting AR seems to improve outcomes in TNBC (1)(2)(3)(4)(5)(6)(7). Despite the prevalence and clinical significance of AR expression in breast cancer, preclinical evidence supporting the use of ARtargeting agents and potential biomarkers of response to AR inhibitors in breast cancer are lacking (4).…”
Section: Introductionmentioning
confidence: 99%
“…They found diabetes mellitus in TNBC patients, and it has been suggested that hyperglycemia directly regulates AR levels. This observation is of interest for the present study, in patients, making the protein a candidate for targeted therapy, but its prognostic role is not yet clear (40). Recently, downregulation of AR has been associated with Figure 5.…”
Section: Discussionmentioning
confidence: 92%
“…Emerging evidence of the role of androgens in the development of ER-negative tumors led to consider AR as a viable therapeutic target. The success of preclinical and clinical trials testing for tolerance and antitumor activity of bicalutamide and enzalutamide provided the foundations for phase II clinical trials investigating a possible use of next generation anti-androgen drugs in breast cancer (Proverbs-Singh et al 2015, Chia et al 2015, Rahim & O'Regan 2017. These trials enrolled both ER-negative patients and ER-positive, resistant to anti-estrogen therapy, patients.…”
Section: Anti-androgen Therapy In Breast Cancermentioning
confidence: 99%